2020
DOI: 10.1038/s41590-020-0635-3
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node stromal cells: cartographers of the immune system

Abstract: econdary lymphoid organs (SLOs), including lymph nodes (LNs), spleen and Peyer's patches (PPs), serve as the body's sites of immune cell surveillance. SLOs provide the infrastructure to maintain immune homeostasis and facilitate rapid and effective immune responses. While spleen and PPs serve to filter material in the blood and gastrointestinal tract, respectively, LNs are strategically situated in proximity to lymphatic and vascular branching points to effectively filter antigens and facilitate immune cell en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
300
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(308 citation statements)
references
References 155 publications
8
300
0
Order By: Relevance
“…Stromal cells are critical to lymph node structure, dictating the T and B cell areas and directly regulating immune cell homeostasis and adaptive immune responses 12,13,14 . Stromal cells form the physical scaffold upon which immune cells migrate and produce molecules that dictate the migration and survival of immune cells 15,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Stromal cells are critical to lymph node structure, dictating the T and B cell areas and directly regulating immune cell homeostasis and adaptive immune responses 12,13,14 . Stromal cells form the physical scaffold upon which immune cells migrate and produce molecules that dictate the migration and survival of immune cells 15,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Having identified two subsets of human CXCR5 + CD4 + follicular T cells based on their differential expression of CXCR5 and PD-1 ( Supplemental Figure 1 ), we decided to explore the impact of FRCs on both GC-Tfh and R5-PD1 dim cells. Indeed, FRCs express high levels of adhesion molecules, extracellular matrix components, and LN chemokines, and promote B and T cell recruitment, adhesion, and survival ( 7 , 21 , 22 ) in both T-cell zone, inter-follicular area, and at follicle border, the place of T-cell priming for Tfh differentiation. In addition, FRCLs obtained by in vitro differentiation of uncommitted TSCs have been proposed as a good model to perform functional FRC evaluation ( 16 , 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some preclinical findings have been made that can guide such further studies. Lymph node biology studies suggest important roles for FAP-positive mesenchymal cells in controlling the migration and compartmentalization of T cells [26]. Studies in mouse cancer models have also shown that the extracellular matrix make-up, controlled by fibroblasts, can affect intra-tumoral immune cell migration [43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FAP expression by stromal cells can have a profound indirect effect on the immune compartment of tumors promoting a shift in T-cell phenotypes towards T-regulatory cells [23]. Interestingly, studies on immune-regulatory mesenchymal fibroblast-like cells of lymph nodes suggest that these cells are derived from FAP+ precursor cells [26,27].…”
Section: Introductionmentioning
confidence: 99%